2000
DOI: 10.1007/bf01279899
|View full text |Cite
|
Sign up to set email alerts
|

Organogenesis fromSolanum melongena L. (eggplant) cotyledon expiants is associated with hormone-modulated enhancement of polyamine biosynthesis and conjugation

Abstract: Summary. Eggplant (Solanum melongena L. cv. Violetta lunga 2)cotyledon explants grown on hormone-free medium (controls) or on medium containing either naphthaleneacetic acid alone (root forming) or in combination with zeatin riboside (shoot forming) showed minor differences in free polyamine titres during culture. In contrast, conjugated polyamines (particularly those in the trichloroacetic acid-soluble fraction) accumulated only in hormonetreated explants, but not in controls. The extent and the temporal chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
(13 reference statements)
1
14
0
Order By: Relevance
“…Though the explant biochemical or molecular basis of such differential response as a function of culture time could not be ascertained from the present study, it may be conjectured from the information available from earlier works that endogenous hormonal levels as well as those of polyamines might be changing with culture time and may influence the final response (Fobert and Webb, 1988;Sharma and Rajam, 1995;Momiyamma et al, 1995;Rajam, 1997, 1998;Scoccianti et al, 2000). The present accessions and explant types might provide suitable experimental system to undertake detailed analysis of these biochemical factors.…”
Section: Effect Of Bapmentioning
confidence: 49%
See 1 more Smart Citation
“…Though the explant biochemical or molecular basis of such differential response as a function of culture time could not be ascertained from the present study, it may be conjectured from the information available from earlier works that endogenous hormonal levels as well as those of polyamines might be changing with culture time and may influence the final response (Fobert and Webb, 1988;Sharma and Rajam, 1995;Momiyamma et al, 1995;Rajam, 1997, 1998;Scoccianti et al, 2000). The present accessions and explant types might provide suitable experimental system to undertake detailed analysis of these biochemical factors.…”
Section: Effect Of Bapmentioning
confidence: 49%
“…In S. melongena, regeneration from the cotyledonary explants at different developmental stages ranging from one week old to 30 days old have been reported (Alicchio et al, 1982;Fobert and Webb, 1988;Rao, 1992;Saito and Nishimura, 1994;Momiyama et al, 1995;Sharma and Rajam, 1995;Hitomi et al, 1998;Magioli et al, 1998;Scoccianti et al, 2000;Tarre et al, 2004;Rahaman et al, 2006). Rama Swami et al (2005) reported in vitro response of cotyledons from three week old seedlings of S. surattense.…”
Section: Discussionmentioning
confidence: 99%
“…Also, callus induction response may be affected by the specificity of explants used for shoot regeneration; thus, explants from 30-days old seedlings revealed better callus induction frequency and subsequent regeneration compared with explants from in vitro developed older plants. Further, the differences in callus and organ induction may be a result of genotype or cultural conditions (Franklin et al, 2004;Magioli et al, 1998;Mir et al, 2008;Scoccianti et al, 2000;Sharma, Rajam, 1995). In our case, duration of callus proliferation on cultural media was very important for shoot regeneration.…”
Section: Discussionmentioning
confidence: 71%
“…Different plant in vitro morphogenic systems have been used to study the role of polyamines (PA), which are proposed as a new class of growth regulators involved in differentiation, reproduction, disease resistance and stress (Scoccianti et al 2000). Eggplant tissues may favour a clearer picture of these molecular signals in differentiation processes, considering their ability to regenerate plants in vitro through different morphogenetic processes.…”
Section: Eggplant As a Model Plantmentioning
confidence: 99%